PENGARUH PERTUMBUHAN EKONOMI DAN USAHA MIKRO KECIL MENENGAH (UMKM) TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN BANGKALAN - Lutfiyah, Lutfiyah (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2016)
This study aims to (1) analyze the influence of economic growth on revenue (PAD) in Bangkalan, (2) analyze the effect of Micro Small Medium Enterprises to revenue (PAD) in Bangkalan, (3) analyze the effect of economic growth and Micro Small Medium Enterprises to revenue (PAD) in Bangkalan. The research uses a quantitative approach. The population in this study is economic growth, Micro Small Medium Enterprises (SMEs) and revenue (PAD) Bangkalan. The sample was economic growth, Micro Small Medium Enterprises (SMEs) and revenue (PAD) in 2004-2013. The type of sampling used in this study is purposive sample. The data collection method used adallah documentation method. While the methods of analysis using multiple linear regression analysis technique. The results showed that the economic growth partially significant effect on local revenue Kabupaten Bangkalan. Small and medium micro enterprises had no significant effect on revenue Bangkalan. While the simultaneous growth of small and medium micro enterprises have a significant effect on revenue Bangkalan